Factors That Influence Palm Oil Farmers' Income - Trie Hierdawati; Dani, Rian (Proceeding of The International Conference on Business and Economics, 2023)
This research aims to determine the factors that influence the income of palm oil farmers. The sample used in this research was 87 oil palm farmers. The analysis used in this research is multiple regression analysis. The research results show that land area, capital and labor simultaneously have a significant effect on income with a significance value of 0.000<0.05. Partially, land area has a significant effect on income with a significance value of 0.000<0.05. Partially, capital has a significant effect on income with a significance value of 0.000<0.05. Partially, labor has a significant effect on income with a significance value of 0.003<0.05.